SOURCE ROCK CHARACTERISTICS BASED ON GEOCHEMICAL ANALYSIS AND 1D BURIAL HISTORY MODELING IN THE “NAY” FIELD SOUTH SUMATRA BASIN - Yoza, Nizalia Azzahra; Butarbutar, Elrey Fernando; Sendjadja, Yoga Andriana; Ilmi, Nisa Nurul (Journal of Geological Sciences and Applied Geology, 2023)
The research is located in the "NAY" Field, South Sumatra Basin at NAY 1-4 Wells. This research was carried out with the aim of knowing the characteristics of source rock such as quantity, quality, maturity, and depositional environment using geochemical analysis, then analyzing the burial history in the study area which was visualized in 1D modeling using Petromod. The results showed that the dominant Well has effective source rock in the Talang Akar Formation. The results of the 1-D Burial History modeling show that the NAY-1 Well is entering phase early mature at a depth of 2394 m at the Talang Akar formation in Early Pliocene (4.22 Ma) and starting to enter the mature phase at a depth of 2521 m in Middle Pliocene (3.27 Ma). The NAY-2 well is entering phase of early mature at a depth of 2521 m at the Talang Akar formation in Early Pliocene (2.64 Ma) and this formation is entering the mature phase at a depth of 2600 m which is Late Pliocene (1.32 Ma). The NAY-3 Well is still immature. Then the NAY-4 well entering phase of early mature at a depth of 2255 m at the Talang Akar Formation in Early Pliocene (2.27 Ma) and the Baturaja Formation at a depth of 2166 m in Late Pliocene (1.63 Ma). The results also show that the majority of the hydrocarbons found in this basin have a marine-terrestrial depositional environment.